Unleashing the power of European innovation : how government, industry and science share knowledge to overcome global challenges - Bakker, Fred (Routledge, 2024)
"The world is at a critical juncture where our industrial and economic principles have to be reshaped. Three major transitions are underway: towards the use of alternative energy sources, towards carbon-neutral and sustainable production, and towards digitalized manufacture and distribution. This book explores the ways in which these transitions are taking place in Europe. No single institution can bring about the necessary changes: a productive cooperation between government, industry and (technological) knowledge centres has to be established. In this insightful book, Fred Bakker paints a vivid picture of a wide range of European businesses, industries and research institutes, joining forces to further the transitions. This process of 'Sharing Brainpower' proves to be a unique European strength that needs to be recognised and furthered. Structured in five parts, the book provides a thumbnail sketch of Europe's goals and methods, through a bird's eye view across current initiatives towards the three transitions, to a concluding part in which the workings of Sharing Brainpower are described in terms of a set of 'lessons learned'. It shows how top-down initiatives and the bottom-up approach reinforce one another, with case stories that prove that diversity does not have to mean fragmentation; it is a source of strength. Policy makers, industry advisers, board members, chief innovation officers and students will find much to inspire them and their work in this book. A website with cases, updates and more information is available at sharingbrainpower.eu"-- Provided by publisher.
Keywords: Technological innovations -- Europe.; Entrepreneurship -- Europe.; Sustainable development -- Europe.; elektronické knihy; electronic books